Lokative pronominer og præpositionalfrasens struktur - Nguyen, Michael (Ny forskning i grammatik, 2019)
In this paper, I investigate the syntax of the prepositional phrase in Danish and the locative pronouns her ‘here’, der ‘there’ and hvor ‘where’ in e.g. hertil ‘hereto’. I argue that (a) the directional adverb p is a functional head that projects a pP on top of a PP and takes this PP as its complement; that (b) the locative pronoun moves via an intermediate position within the prepositional phrase before it leaves the prepositional phrase; and that (c) the preposition moves to p (P-to-p-incorporation).